A Modified Fama-MacBeth Model based on the Single-Index Model - Jumaah Mousa , mariam; Yousif Hmood, Munaf (Journal of Economics and Administrative Sciences, 2025)
The aim of this essay is to use a single-index model in developing and adjusting Fama-MacBeth.  Penalized smoothing spline regression technique (SIMPLS) foresaw this adjustment.  Two generalized cross-validation techniques, Generalized Cross Validation Grid (GGCV) and Generalized Cross Validation Fast (FGCV), anticipated the regular value of smoothing covered under this technique. Due to the two-steps nature of the Fama-MacBeth model, this estimation generated four estimates: SIMPLS(FGCV) - SIMPLS(FGCV), SIMPLS(FGCV) - SIM PLS(GGCV), SIMPLS(GGCV) - SIMPLS(FGCV), SIM PLS(GGCV) - SIM PLS(GGCV). Three-factor Fama-French model—market risk premium, size factor, value factor, and their implication for excess stock returns and portfolio returns—were estimated on the Iraqi Stock Exchange using the modified Fama-MacBeth.  SIMPLS(FGCV)-GGCV performed best based on the findings.  Results also revealed the statistical significance of the three factors of the Fama-French model, which enhanced the explanatory power of the model in terms of the performance of Iraq Stock Exchange